2011
DOI: 10.5897/ajb11.1282
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the psoRPM1 gene for resistance to root-knot nematodes in wild myrobalan plum (Prunus sogdiana)

Abstract: Several root-knot nematode (Meloidogyne spp.) resistance genes have been discovered in different stone fruit crops. However, none of them has yet been cloned and they were only located on the chromosomes. In this study, a candidate root-knot nematode resistance gene (designated as psoRPM1) was isolated from the individual plant of Xinjiang wild myrobalan plum (Prunus sogdiana) by degenerate PCR amplification combined with the RACE technique. The gene had a typical NBS-LRR structure and high homology with Mi-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Interspecies comparative genomic analysis revealed that HSPs, RPM1, BIN2, and BRI1 underwent significant expansion in gene copy number in Shanmei genome. The HSP genes can enhance the heat stress ability of plants [20], while the RPM1 gene can reduce the damage caused by pathogens [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interspecies comparative genomic analysis revealed that HSPs, RPM1, BIN2, and BRI1 underwent significant expansion in gene copy number in Shanmei genome. The HSP genes can enhance the heat stress ability of plants [20], while the RPM1 gene can reduce the damage caused by pathogens [22].…”
Section: Discussionmentioning
confidence: 99%
“…RPM1 is a resistance gene that improves the resistance to root-knot nematodes in wild myrobalan plum [22]. In summary, the expansion of these genes may contribute to the environmental adaptability of Shanmei in the wild.…”
Section: Expanded Gene Families In Flavonoid Biosynthesis and Stress ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the Mi‐1.2 gene, but not the Mi‐1.1 gene, confers resistance to RKN (Lavrova et al, 2016). The genes Ma , PsoRPM1 , PsoRPM2 , and PsoRPM3 cloned from Myrobalan plum, as well as CaMi from pepper “PR 205,” were all identified as RKN resistance genes (Chen et al, 2007; Claverie et al, 2011; Li et al, 2011; Xiao et al, 2021; Zhu et al, 2017). These genes were found to contain the nucleotide binding and leucine‐rich repeat (NB‐LRR) domain.…”
Section: Introductionmentioning
confidence: 99%